If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + p = 27 Solving 23 + p = 27 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + p = 27 + -23 Combine like terms: 23 + -23 = 0 0 + p = 27 + -23 p = 27 + -23 Combine like terms: 27 + -23 = 4 p = 4 Simplifying p = 4
| V=0.50r(2)h | | 7(3x+3)=21x+21 | | p^2-1/9 | | 58=5m+52 | | 14z-2/7=5/7 | | (7x+5)+(9x+2)=81 | | 2x+(-2x+1)=1 | | 6m+54=4m | | -87=-5x-3x+9 | | 16+18=4x-6 | | x^2=16/0.49 | | 8m+60=20m | | 2/5a-42 | | 32r+4s=36r | | S+15=8 | | -2x-3+-3x=17 | | 20.8+2z=24 | | 7t=80+91 | | 17/12m=1/2m-11/4 | | 6x-4(4+2x)=-10(3x+10) | | -2x^2-4x+24=0 | | Y=45x+145 | | 2+11b= | | 10-2x=25 | | y=3y+8 | | 8-7x+2x=38 | | 50+3(x+6)=4x-5 | | 10-11(4+n)=8(7-7n) | | 4x-2x+6xy+21x+(-9)-9= | | 2x^2+9x-396=0 | | 1/2x-8=-5 | | -6(x+9)-9x=-3(x+2) |